Analytical Model Of The Surface And Center Potential For GAA Si-Nanowire Mosfets - Ritu Yadav, Dr. Kiran Ahuja, Dr. Davinder Singh (International Journal of Advanced Science and Technology, 2020)
Integrated circuits are in demand to be invetigated for its economical performance. Therefore, it is vialbe to experiment on ternary based operations[7]. A ternary half adder based on ternary multiplexer and logic primitives is proposed and its performance is analyzed in detail. This proposed ternary half is sensibly designed with the simplified expressions using the ternary k-map. The combinational logic blocks for the SUM and CARRY are designed, verified, constructed and simulated with Tanner EDA (130nm) at 1.2 V.Analytical modeling of potential distribution has been derived by using Poisson equation for short channel gate all around (GAA) Si-nanowire MOSFET. The architecture of the proposed device based on equal number of gates have been utilized to calculate effective natural length (λc). Comparison of center and surface potential along the channel length have been obtained by using ENL based on Poisson equation with suitable boundary condition. Further to investigate the Figure of merits, such as ON/OFF current, DIBL, subthreshold slope and threshold voltage is done by using different silicon thickness. The effect of physical devices parameters such as radius of silicon (tSi), gate oxide thickness (tox) ,total channel length (L) and drain biases (Vds) have been investigated on the devices by using MATLAB